Yolk–shell nanospheres with soluble amino-polystyrene as a reservoir for Pd NPs1. Issue 45 (20th May 2015) - Lan, Guojun; Zhang, Xiaoming; Zhang, Xiaomin; Li, Mingrun; Li, Ying; Yang, Qihua
<x xml:space="preserve">Abstract</x> Pd NPs immobilized in yolk–shell nanospheres confined with soluble amino-polystyrene could efficiently catalyze the selective hydrogenation of acetophenone.